Analysis of the mechanical behavior and effect of cyclic fatigue on the implant-abutment interface = Análisis del comportamiento mecánico y efecto de la fatiga cíclica en la interface implante-pilar - Germán Sandoval, Ramón
Purpose: The seal of the interface formed at the implant-abutment connection is essential for the long-term success of the implant-supported restoration. The aim of this study was to analyze the mechanical behavior and the effect of cyclic fatigue before and after in the marginal fit of implant-abutment according to the manufacturing technique of the abutment. Materials and methods: Machined titanium abutments (DENTIS), cast abutments with Nickel-Chromium alloy (VeraBond II), and manufacturing custom milled Zirconia abutments (Zirkonzahn) were evaluated. The implant-abutment assemblies were subjected to cyclic loads of 133 N at a frequency of 19.1 Hz for 200,000 cycles. The microgap was measured using Scanning Electronic Microscope and the distribution of compressive stress by the three-dimensional Finite Element (FE) method. Results: The microgap measurement values of the machined abutments were 1.62μm and 1.92μm, cast abutments were 14.14 μm, and 28.44 μm, and the milled abutments were 14.18μm and 20.15μm before and after cyclic fatigue, respectively. Only the cast abutments and the machined abutments showed a statistically significant difference before and after cyclic fatigue (p≤0.05). The FE analysis showed that the critical areas of compressive stress were located at the implant-abutment connection, increasing in the cast abutments and decreasing in the milled and the machined abutments. Conclusion: Cyclic fatigue exerts an effect on the dimensions of the microgap at the implant-abutment interface before and after loading; this microgap depends of the type of abutment material and the manufacturing technique.